Economic, Social and Cultural Rights in the Context of the Peace Process with the CPP-NPA-NDFP: Issues and Concerns - Candelaria, Sedfrey M (Archīum Ateneo, 2018)
The peace process between the Government of the Republic of the Philippines (GRP) and the Communist Party of the Philippines-New People’s Army-National Democratic Front of the Philippines (CPP-NPA-NDFP) was formally opened in 1995 in Brussels, Belgium. While several agreements have been signed between the GRP and the CPP-NPA-NDFP since then, only one major substantive agreement, i.e., the Comprehensive Agreement on Respect for Human Rights and International Humanitarian Law (CARHRIHL) has been accomplished. Under the Hague Declaration of 1992, three (3) more substantive agreements are necessary to achieve a just and lasting peace, namely: (a) Comprehensive Agreement on SocioEconomic Reforms (CASER); (b) Comprehensive Agreement on Political and Constitutional Reforms (PCR); and (c) End of Hostilities (EOH). During the round of negotiations undertaken under the presidency of Rodrigo Roa Duterte, the negotiating panels of both parties to the peace process emphasized the crucial impact of a CASER in the course of the process. Existing drafts on CASER have been intensively discussed with some tentative consensus points which are worth inquiring into. The purpose of this paper is to examine the contentious issues which require public deliberation as the negotiations hopefully progress in the near future. In the course of the present writer’s inquiry, the dynamics of negotiations and achieving compromises by both parties will be emphasized. Focus will be made on the following areas of concern: (a) Agrarian and Rural Development; (b) Rural Industrialization; (c) National Industrialization; (d) Environmental Protection; (e) Rights of Various Sectors (e.g. working people, women, children, elderly, disabled, indigenous peoples, etc.); and, (f) Policy on Foreign Economic Relations. As a conclusion, the present writer will offer some strategies, in order to address contentious points identified in the text of the CASER drafts.